Menestyksekkään peliprojektin johtaminen eli Peliprojektin säännöt - Koskenkorva, Risto (2006)
Leading a succesful game project requires surprisingly many things in addition to the leading and management skills and qualities. Leading usually means working with people and taking care of their well-being while management often means scheduling and information handling [28]. Especially important are the general views of the structure of the game and project as well as the people led. It's also essential to perceive the whole as well as the details. The term success can be easily be de ned in a way that is useful for the project but there are still many aspects to be considered, like a game from the market point of view or a project as a quality process. In the center of the game project are computer games and the di erent elements that can be found in them. The structure of a game project is actually very much like the structure of the game. Each person working in a game project, so called game developer, must be an expert in his or her own eld. Because of the groups functionality and respect the production leaders and managers have to know at least the same things their special group know. This sets a challenge for acquiring and providing the right kind of education. It is impossible for the actual project leader to everything about every specialty of every group in the project. Further this sets even more harder requirements for the abilities and skills of the leader. A leading position can be given to many kinds of people, but what distinguishes a good leader and what characteristics are required from them? What are the basics of leadership? Because of their con icting natures and constant need of precise control, leading and managing as well as nding a working balance between the two may prove to be too demanding a challenge for personnel, who would otherwise qualify for leaders. Leading a game project is possible only through managing and leading developers working on di erent areas and in di erent geographical locations. In completing this task, the leader can use computers and information technology to their fullest. In game industry, the leader of the game development project is often in a role comparable to that of a game producer, whose responsibility is to sustain the overall idea behind the game product. It is vital to understand that the position of a leader consists of varying tasks and possibly even too many roles, which depend on the nature of the project. This Master's Thesis focuses on leading a game project from the viewpoint of the leader and thus limited covers all aspects of a game project. Central topics are the structure of the product (i.e. the game), its consistency and the challenges it poses in the actual game project and, naturally, leader and leadership. Other topics are the game developer, succesfullness of a game project and information technology as a tool for improved leadership and management. The research is divided in seven sections: tietokonepelin elementit (The elements of a PC game), pelinkehitt aj an koulutus (Game developer education), johtajuuden alkeet (Basics of leadership), johtaminen vastaan hallinnoiminen (Leading vs. Managing), tietotekniikan hy odynt aminen (Appliances of Information Technology), peliprojektin rakenne (Structure of a Game Project) and peliprojektin menestyminen (Succesfullness of a Game Project). The sections also contain literature overviews and a research report [11] made by several people (Mikko Tiusanen, Risto Koskenkorva, Risto Per anen ja Juha Halmetoja) - "IGIOS peliprojektin rakenne (The structure of IGIOS game project)". Because of the stucture, some results are already introduced in the subsections. In some of the sections, IGIOS game project (http://www.igios.com) is used as a sample scenario. All sub-sections of the research are essential to the research process and together they form a possible solution for leading a successful game project. In short, a lot depends on a leader who, with the help of information technology, is able to lead game developers working in the project into completing the elements of a game and thus completing a succesfull game project.